Perancangan Sistem E-Commerce Berbasis Web pada Toko Pakaian Online - Nurjamiyah; Fadhilah Zuhdiyyah Lubis (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
The development of information technology encourages business actors to utilize digital media in order to increase effectiveness in the sales process. Online clothing stores are one type of business that requires a sales system capable of reaching a wider range of consumers and facilitating transaction processes. This study aims to design a web-based e-commerce system for online clothing stores to support the management of product data, orders, and sales transactions in a computerized manner. The methods used in this study include system requirements analysis, system design using Unified Modeling Language (UML), database design, and user interface design. The results of this study are a web-based e-commerce system design that provides various features such as product catalogs, shopping carts, ordering processes, and data management by administrators. The implementation of this system is expected to improve sales process efficiency, expand marketing reach, and facilitate customers in conducting online clothing purchase transactions.